Free‐volume structure of polyvinylpyrrolidone‐capped glassy As2Se3 nanocomposites prepared by mechanical milling. Issue 12 (2nd April 2019) - Shpotyuk, Oleh; Ingram, Adam; Bujňáková, Zdenka; Baláž, Peter; Shpotyuk, Yaroslav; Slobodzyan, Dmytro; Woźny, Mariusz; Boussard‐Pledel, Catherine; Bureau, Bruno
Abstract : The method of positron annihilation lifetime (PAL) spectroscopy was first employed to study atomic‐deficient free‐volume structure of nanocomposites prepared by high‐energy mechanical milling of glassy g‐As2 Se3 in water solution of polyvinylpyrrolidone (PVP). The formalism of x3‐x2‐CDA (coupling decomposition algorithm) describing conversion of bound positron‐electron (positronium Ps) states into positron traps was applied to identify free‐volume elements in pelletized PVP‐capped g‐As2 Se3 nanocomposite in respect to parent dry‐milled g‐As2 Se3 . Under wet milling, the internanoparticle Ps‐decaying sites in preferential PVP environment were shown to replace free‐volume positron traps in dry‐milled g‐As2 Se3 with defect‐specific positron lifetime of 0.352 ns, corresponding to diatomic/triatomic vacancies in g‐As‐Se matrix. POLYM. ENG. SCI., 59:2438–2442, 2019. © 2019 Society of Plastics Engineers